Modeling ammonia oxidation over a Pt (533) surface - Rafti, Matias (2012)
We present a new reaction model for ammonia oxidation on a Pt (533) surface and perform numerical simulations using mean field equations. Kinetic parameters were taken from experiments and Density Functional Theory (DFT) calculations. The model is based on an oxygen-activated ammonia decomposition and includes NHx (x = 0, 1, 2) intermediates. Reaction rates and coverages obtained from calculations show semiquantitative agreement with values from kinetic and in-situ XPS measurements up to 0.1 mbar pressures. Pathways for ammonia oxidation were analyzed by varying kinetic parameters in the model, which provides new insights into the relative importance of different reaction steps.